2021
DOI: 10.3390/w13050656
|View full text |Cite
|
Sign up to set email alerts
|

Electrocoagulation as a Promising Defluoridation Technology from Water: A Review of State of the Art of Removal Mechanisms and Performance Trends

Abstract: Fluoride ions present in drinking water are beneficial to human health when at proper concentration levels (0.5–1.5 mg L−1), but an excess intake of fluoride (>1.5 mg L−1) may pose several health problems. In this context, reducing high fluoride concentrations in water is a major worldwide challenge. The World Health Organization has recommended setting a permissible limit of 1.5 mg L−1. The application of electrocoagulation (EC) processes has received widespread and increasing attention as a promising trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 97 publications
(274 reference statements)
0
28
0
Order By: Relevance
“…The economic analysis presented for the replacement of conventional coagulation with electrocoagulation for coke oven wastewater showed that if the process was applied to plants with an external power supply, its economics were not yet justified, but if a coke oven plant possessed its own power supply, the electrocoagulation treatment was more beneficial than conventional coagulation. However, it is worth noting, that the process of electrocoagulation is also used in other industries [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The process has considerable potential for practical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic analysis presented for the replacement of conventional coagulation with electrocoagulation for coke oven wastewater showed that if the process was applied to plants with an external power supply, its economics were not yet justified, but if a coke oven plant possessed its own power supply, the electrocoagulation treatment was more beneficial than conventional coagulation. However, it is worth noting, that the process of electrocoagulation is also used in other industries [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The process has considerable potential for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the electrocoagulation process is widely used for different types of pollution [ 29 , 30 , 31 ]. It has found application in many different industries, including the cleaning and neutralization of oil emulsions used in machining and abrasive handling, wastewater from the textile industry, wastewater from agro-food processing businesses, wastewater from car washes, heavy metals, and other pollutants such as coke oven wastewater [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this process has not been widely applied for drinking water treatment due to several factors that must be considered, such as the sacrificial electrodes being in compliance with the WHO guidelines 72 or the possibility that the treated effluents could still present high concentrations of metal ions that would need further treatment, 70,73 leading to hybrid schemes 74,75 being needed to meet the standards for drinking water set by legal entities. 76 Currently, there are a few small capacity plants for the defluorination of potable water described by Castañeda et al 72 in India and Africa; meanwhile, there are several studies on the field devoted to the removal of turbidity, organic matter, 77 nitrate, 78,79 pathogens, 80 etc.…”
Section: Progressive Steps On Ec Treatmentmentioning
confidence: 99%
“…87 Even though EC has limited chemical cost requirements (or none ehatsoever) compared to CC, it might require higher maintenance or further sludge handling costs. 73 In Table 4, differences with regards to flocs and sludge characteristics are presented.…”
Section: Ec Sludge Treatmentmentioning
confidence: 99%
“…Various techniques have been developed to remove excess fluoride from drinking water, such as adsorption, coagulation, ion exchange, microbial-induced precipitation [10,11], electrocoagulation [12], electrostatic unit [13] and electrodialysis [5,14]. Among these techniques, adsorption is effective, economical, convenient, and environmentally friendly [3,4,15,16].…”
Section: Introductionmentioning
confidence: 99%